HUBUNGAN TINGKAT PENGETAHUAN DAN DUKUNGAN KELUARGA DENGAN PERILAKU PEMBERIAN MP-ASI DINI PADA IBU BAYI 0-5 BULAN - Sari, Juwita Nopia; Barbara , Maria AD (Seroja Husada: Jurnal Kesehatan Masyarakat, 2024)
Early provision of MPASI has many negative impacts on the baby's health, because the baby's digestion is not yet ready to accept food other than breast milk. Several factors that cause early provision of MP ASI include knowledge and family support. The aim of this research is to determine the relationship between the level of maternal knowledge and family support with the behavior of providing early MPASI in the Nagrak Community Health Center Working Area, Nagrak Village in 2024. This research method is quantitative with an analytical observational research design. The population of this study was 396 mothers with babies aged 0-6 months, with a sample of 84 people. Sampling techniques of proportionate stratified random sampling. Data analysis uses univariate and bivariate analysis. The results of the study showed that a small percentage (32.1%) of baby mothers gave early MPASI, the majority (39.3%) of baby mothers lacked knowledge and a small percentage (42.9%) of baby mothers had families who did not support giving MPASI. Chi squrae test results of knowledge (p=0.001) and family support (p=0.000). There is a relationship between knowledge and family support and the behavior of giving early MPASI. The role of health workers as information providers is very necessary to socialize the MP ASI program according to age.